Hand Puppet Media to Improve Indonesian Language Learning Outcomes of Grade III Elementary School Students - Putu Krishna Aditya; I Made Suarjana; Ni Made Dainivitri Sinta Sari (Undiksha Press, 2025)
Indonesian language is a strategic subject in developing language skills among elementary school students. However, students' learning outcomes in listening and speaking remain low due to the lack of innovation in teaching methods and learning media. This study aims to analyze the effect of using hand puppet media on the Indonesian language learning outcomes of third-grade elementary school students. The study employed a quantitative approach with a quasi-experimental design, specifically the posttest-only control group design. The research subjects were third-grade elementary school students selected through cluster random sampling. Data collection techniques included learning outcome tests and documentation. The data were analyzed using descriptive and inferential statistics, including an independent t-test. The results showed that tcount = 4.96 > ttable = 2.021 and p = 0.000, indicating that the use of hand puppet media had a significant effect on improving students' Indonesian language learning outcomes. Therefore, it can be concluded that hand puppet media significantly enhances students' achievement in learning Indonesian. The implication of this study highlights the importance of using creative and contextual learning media, such as hand puppets, to create active, enjoyable, and meaningful learning experiences at the elementary school level.